RANCANGAN RANGKAIAN ANTI BOUNCING UNTUK RANGKAIAN DIGITAL - Redaksi Tim Jurnal (Sutet, 2017)
Push-On switches or toggle switches and mechanical relays are mechanical contacts made of metal which, when supplied with electric current, will result in a spike of electrical sparks, called Bouncing Effects. Bounce effects are often a problem in digital circuits, especially in digital electronics circuits, because these Bounce Effects will cause the value of data or signals coming into the circuit inaccurate or indeterminate, when the mechanical switch is pressed as input data. This will undoubtedly lead to undesirable conditions and must be overcome with an electronic circuit called De-Bounce for the data or input signal to be more certain.